Effect of triplet encapsulated atoms in [60] fullerenes: a theoretical analysis - Jalbout, Abraham F. (Eclética Química, 2008)
The present investigation reports on the interaction of the C/O triplet atoms inside of the [60] fullerene (C60) species with small polar molecules (H2O, CH3OH, HF, NH3) using Density Functional Theory (DFT) calculations. The calculations show that in all the computed cases the encapuslated complexes with the molecules are more stable than without internal atoms.